ANALISA PERBEDAAN LPS (LAST PLANNER SYSTEM) DENGAN SISTEM KONVENSIONAL SERTA PENGARUH CPM DAN BAR CHART PADA LPS - Sadhu Adwitya A; M. Agung Wibowo; Syafrudin Syafrudin (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
Two generally method / tools which used in project construction management system in Indonesia and the name are CPM (critical part method) or network planning and Bar Chart. The system used general method called conventional management system. Nowadays, was appeared one of a new system which seldom to applied in Indonesia, it is called LPS (last planner system). This research, researcher doing analyzed the differences between LPS and conventional management system. The result which obtained in this research are LPS dominated to accentuates team collaborative in the scheduling planning, resource allocation, control and enhance of work productivity, issue solved, regularly scheduling planning. Conventional management system more rely on the way CPM and Bar Chart working in that system with project manager decision. Planning of the schedule in this system doing by scheduling team. rescheduling in this system is not routine, it’s depend by construction progress. CPM and Bar Chart methods is influence on LPS. The both of methods was appeared in master scheduling, look a head scheduling, weekly work planning, shielding production, workable back log, percent plan completed and reliable promise process